Decreased IFNI? production correlates with diminished production of cytokines by dendritic cells in patients infected with hepatitis C virus and receiving therapy - Hammond, T.; Lee, S.; Watson, M.; Flexman, J.; Cheng, W.; Price, Patricia (2011)
Toll-like receptor (TLR) expression and the signalling pathways that lead to the production of accessory cytokines by antigen-presenting cells (APCs) both have potential to limit T-cell responses to viral antigens. Here, expression of TLR and retinoic acid inducible gene I (RIG-I) and responses evoked through these proteins were evaluated in patients chronically infected with HCV, before and during pegylated interferon-a (IFN-a) and ribavirin therapy. Expression of TLR2, 3, 4, 7, 9 and RIG-I on APCs and cytokine production by DCs were measured by flow cytometry. Production of IL-12 by myeloid dendritic cells (mDCs), IFNa by plasmacytoid cells (pDCs) and IFNI? by peripheral blood mononuclear cells was measured after stimulation with TLR ligands. IFNÎ ELISpot responses to HCV and CMV antigens declined on therapy. TLR and RIG-I expression on mDCs, pDCs, B cells and monocytes was either similar or higher in patients than that in controls and generally increased during therapy. Therapy impaired IL-12 and IFNa production by DCs and reduced production of IFNI? by PBMCs after stimulation with ligands for TLR3, TLR7/8, TLR9 and RIG-I. This was independent of whether patients attained a sustained virological response. HCV disease and interferon-based therapy reduced IFN-? responses to HCV antigens and TLR agonists. This was not accompanied by reduced expression of pertinent TLR but correlated with diminished production of co-stimulatory cytokines by DCs stimulated via TLR. © 2010 Blackwell Publishing Ltd.